Installation colour, space and environment - Sedon @ M. Dom Mohd Fauzi, Said Tajul Shuhaizam, Ramli Harozila, Isnin Siti Fazlina (N/A, 2014)
Installation colour, space and environment by Sedon @ M. Dom Mohd Fauzi, Said Tajul Shuhaizam, Ramli Harozila, Isnin Siti Fazlina,